Social Justice Counseling and Advocacy: Developing New Leadership Roles and Competencies - Judith A. Lewis; Manivong J. Ratts; Derrick A. Paladino; Rebecca L. Toporek (Journal for Social Action in Counseling and Psychology)

(untitled)
The fusion of scholarship and activism represents an opportunity to reflect on ways in which counselors and psychologists can begin to address the multilevel context faced by clients and client communities. Counselors and psychologists have embraced, and sometimes resisted, the wide range of roles including that of advocate and activist. This article reflects on a process that engaged workshop participants in examining the American Counseling Association Advocacy Competencies and exploring the possibilities of advocacy on behalf of their own clients. Further, the article presents recommendations for actions developed by participants through application of workshop principles regarding social action in the larger public arena. The workshop was a part of the National Multicultural and Social Justice Leadership Academy in 2010.